THE INFLUENCE OF SOCIAL STATUS AND SOLIDARITY TO THE QUANTITY OF UTTERANCES IN JANE AUSTEN’S NOVELS - Citra Suryanovika; Novita Julhijah (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
The main focus of the research is the female main characters in six novels of Jane Austen. The study basically aimed to identify the influence of Holmes’s social status and solidarity on the quantity of utterances. The result shows that 1,738 utterances from 266 Elinor Dashwood’s utterances, 368 Elizabeth Bennet’s utterances, 194 Fanny Price’s utterances, 473 Emma Woodhouse’s utterances, 113 Anne Elliot’s utterances and 324 Catherine Morland’s utterances. Accordingly, high social status of Emma Woodhouse produced the greatest quantity of utterances compared to other characters, and Fanny Price’s lowest social status is in the fifth position of six characters. The analysis of solidarity showed that 66.7% utterances come from characters with high solidarity scale, while 33.3% utterances belong to characters of low solidarity scale. In short, characters’ social status and solidarity are not two main factors in determining the quantity of utterances. The quantity of utterances was also determined by the interest and curiosity.Keywords: Social Status, Solidarity Scale, Utterance, Jane Austen. PENGARUH STATUS SOSIAL DAN SOLIDARITAS TERHADAP KUANTITAS UJARAN DALAM NOVEL-NOVEL JANE AUSTENAbstrakFokus penelitian pada ujaran yang disampaikan oleh tokoh utama perempuan dalam enam novel Jane Austen. Penelitian bertujuan menelaah pengaruh status sosial dan solidaritas pada kuantitas ujaran. Hasil penelitian menunjukkan 1,738 dengan rincian 266 ujaran Elinor Dashwood, 368 ujaran Elizabeth Bennet, 194 ujaran Fanny Price, 473 ujaran Emma Woodhouse, 113 ujaran Anne Elliot, and 324 ujaran Catherine Morland. Berdasarkan peringkat, status sosial tinggi Emma Woodhouse menghasilkan jumlah ujaran paling banyak, dibandingkan dengan lima tokoh lainnya, namun Fanny Price dengan status sosial paling bawah berada di peringkat kelima dari enam tokoh yang ditelaah. Telaah keakraban menunjukkan 66,7% jumlah ujaran dengan skala solidaritas tinggi, dan 33,3% ujaran dengan skala solidaritas rendah. Berdasarkan hasil analisa, dapat disimpulkan bahwa penentu kuantitas ujaran bukan hanya ditentukan oleh status sosial dan solidaritas karakter, tapi juga ditentukan oleh ketertarikan dan rasa penasaran. Kata kunci: Status Sosial, Skala Solidaritas, Ujaran, Jane Austen.